Medication adherence and management of blood glucose in type 2 diabetes mellitus - Erwan, Fragestha; Andoko, Andoko; Triyoso, Triyoso; Kurniasih, Dennti (JOURNAL OF Mental Health Concerns, 2025)
Background: Type 2 diabetes mellitus is a prevalent chronic disease that can lead to serious complications if not properly managed. One of the key factors in diabetes management is patient adherence to medication. Purpose: To analyze the relationship between medication adherence and blood glucose levels in patients with type 2 diabetes mellitus. Method: A analytical survey design with a cross-sectional approach. A total of 146 respondents were selected using purposive sampling. Data were collected using questionnaires and analyzed using univariate and bivariate analysis with the chi-square test. Results: A total of 61.0% of respondents demonstrated high medication adherence, and 48.6% had low blood glucose levels. Statistical analysis showed a p-value of 0.001 (p < 0.05), indicating a significant relationship between medication adherence and blood glucose levels. Conclusion: There is a significant relationship between medication adherence and blood glucose levels in patients with type 2 diabetes mellitus. Keywords: Adherence; Blood Glucose Levels; Type 2 Diabetes Mellitus.